Safeguarding Homeland Security Governors and Mayors Speak Out - Hakim, Simon; Blackstone, Erwin A. (Springer New York : Imprint: Springer, 2009)
This book brings together the technological and managerial innovations suggested and applied by the nation's leading governors and mayors in their own words. It includes models for public-private partnerships to improve preparation for, response and recovery from major natural disasters and terrorist attacks. These leaders in innovation point out how the 9/11 communication problems that contributed to the catastrophe have been addressed, including the use of volunteer agencies and volunteers to supplement governmental efforts, which is a recurring theme of the book. The book makes specific recommendations of services usually provided by public emergency agencies that are private in nature and could be shed by government while often being provided by the private sector. The book further suggests public services that are under the responsibility of governments but could be delivered more efficiently by contracting them out under competitive conditions and highlights incentives for greater involvement of the private sector in the delivery of emergency services.